Contribution of Activities of the Taklim Assembly Contact Agency (BKMT) in Social-Religious Development - Abdul Aziz; Iswantir (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This paper examines the contribution of the activities and activities of the Taklim Assembly Contact Agency (BKMT) in developing practice (muamalah) and the religious social life of the people of West Sumatra. As for what makes this research interesting, it is caused by changes in social interaction and changes in culture or community culture, including the people of West Sumatra. West Sumatra with its monumental philosophy says that the society it aspires to is a civilized society and upholds the guidelines of syarak (Islam). It is in this context that the contribution of the BKMT in west Sumatra becomes the object of research in this paper. This includes what factors are targeted and become the concentration of BKMT in west Sumatra’s activities. The research process is carried out in a simple way, then it will be revealed using quantitative methods, where the data and sources are obtained through  questionnaires which are then processed systematically to obtain empirical (reality) content.  In this study, it can be concluded that the contribution BKMT is to prioritize learning activities that are eternal (forever), this is evidenced by the target of congregations and da'wah participants in every religious activity of the BKMT which has succeeded in reaching all levels of society. Then by rotating (safari) its da'wah activities in various remote areas which are also supported by local stakeholders, the contribution of the West Sumatra BKMT has a good value, even relatively being one of the elements of developing non-formal education